Design for lean production na melhoria de um componente automóvel - Correia, Mariana (2015)
The optimum design, associated to low cost high quality and quick delivery are imperative for competitive companies. These targets lead to the development of new project methodologies that focus on the customer’s needs. Today’s organizations need to deal with dynamic and competitive environments. In order to be successful, companies must be strategically aware. They must understand how changes in their environment are unfolding and they should know the customers’ importance. The integration of various tools on project development is a new key way to improve quality and increase profit. Thus, the goal of this project was to develop a project methodology that could integrate various project methods and at the same time could improve the performance of the steering angle sensor, reducing its cost and improving its quality regarding its production process. It can be said that the improvement of the component in respect of the reduction of the noise emitted allows an increase in the quality of it and consequently an increase in customer satisfaction. But the most important challenge was this improvement has happened in the product development phase. Thus, in the product development phase, it was possible to reduce the waste with the lean tools during production as the movement, inventory, shipping and defects consumption materials and energy, and this way it is possible do more with less. Thus, it was found that by integrating design tools such as TRIZ and QFD, in the product development phase, are developed concepts geared to the needs of customers at the same time that reduce waste that do not add value to the product.